2017
DOI: 10.1080/17588928.2017.1319350
|View full text |Cite
|
Sign up to set email alerts
|

Cluster success: fMRI inferences for spatial extent have acceptable false-positive rates

Abstract: In an editorial (this issue), I argued that Eklund, Nichols, and Knutsson's 'null data' reflected resting-state/default network activity that inflated their false-positive rates. Commentaries on that paper were received by Nichols, Eklund, and Knutsson (this issue), Hopfinger (this issue), and Cunningham and Koscik (this issue). In this author response, I consider these commentaries. Many issues stemming from Nichols et al. are identified including: (1) Nichols et al. did not provide convincing arguments that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(115 citation statements)
references
References 4 publications
2
113
0
Order By: Relevance
“…51 Based on the ASL recording parameters, a cluster size of k = 44 was required to cluster correct the results at a threshold of P ≤ .05 (cluster-corrected). 51 Based on the ASL recording parameters, a cluster size of k = 44 was required to cluster correct the results at a threshold of P ≤ .05 (cluster-corrected).…”
Section: Cbf Quantification-cbf Was Calculated On a Voxel-wise Basismentioning
confidence: 99%
See 2 more Smart Citations
“…51 Based on the ASL recording parameters, a cluster size of k = 44 was required to cluster correct the results at a threshold of P ≤ .05 (cluster-corrected). 51 Based on the ASL recording parameters, a cluster size of k = 44 was required to cluster correct the results at a threshold of P ≤ .05 (cluster-corrected).…”
Section: Cbf Quantification-cbf Was Calculated On a Voxel-wise Basismentioning
confidence: 99%
“…51,52 In brief, the automated surface-based reconstruction processing stream consists of skull stripping, Talairach space transformation, gray matter (GM), white matter (WM) and cerebral spinal fluid (CSF) boundaries optimization, segmentation of subcortical structures, tessellation, and surface deformation. 51,52 In brief, the automated surface-based reconstruction processing stream consists of skull stripping, Talairach space transformation, gray matter (GM), white matter (WM) and cerebral spinal fluid (CSF) boundaries optimization, segmentation of subcortical structures, tessellation, and surface deformation.…”
Section: Cbf Quantification-cbf Was Calculated On a Voxel-wise Basismentioning
confidence: 99%
See 1 more Smart Citation
“…ERP studies, usually focusing on poststimulus brain activity, showed that visuospatial attention enhances activities originating in dorsal and ventral extrastriate pathways, indexed by the P1 and the N1 components. Furthermore, visuospatial attention does not affect the afferent activities originating in the primary visual area (V1), indexed by the C1 component (Baumgartner, Graulty, Hillyard, & Pitts, ; Di Russo, ; Gómez‐Gonzalez, Clark, Fan, Luck, & Hillyard, ; Pitts & Hillyard, ; however, see Slotnick, for opposite results). Regarding attention effects on frontal areas, ERP evidence is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of them identified this component as the later and multimodal decisional process of the anterior insula. Summarizing, studies in this field associated each of the three prefrontal ERPs with specific and known stages of processing of the anterior insula: the pN1 with perceptual awareness, the pP1 with the conscious experience of the sensory-motor coupling, and the pP2 with the decisional process of categorization and evidence accumulation Bianco, Berchicci, Perri, Quinzi, & Di Russo, 2017a;Di Russo et al, 2016,2017Gonçalves et al, 2018;Perri, Berchicci, Bianco, Quinzi, et al, 2018;Perri, Berchicci, Lucci, Spinelli, & Di Russo, 2015a,2015bRagazzoni et al, 2019;Sulpizio et al, 2017). So far, these prefrontal components were measured using centrally displayed stimuli, without manipulating spatial attention; thus, the question is open on whether spatial attention may affect them.…”
Section: Introductionmentioning
confidence: 99%